Ukama Ustawi’s Learning Alliance: scoping study - final report - Kumwenda, H.; Kakuwa, B.; Odeke, M.; Podisi, B.; Nohayi, Ngowenani (International Water Management Institute (IWMI). CGIAR Initiative on Diversification in East and Southern Africa, 2024)
This scoping study for Ukama Ustawi’s Learning Alliance (UULA) was inspired by the need for better collaboration and experience sharing among research providers dedicated to creating agricultural knowledge and its dissemination in the East and Southern Africa (ESA) region. It provides recommendations on the potential institutional arrangements for setting up a Learning Alliance (LA) to achieve the desired end and to also guide Knowledge Management and Learning (KML) around diversified maize farming systems. The recommendations were developed following a desk review of relevant literature and analysis of data collected from key implementing partners at the national and regional levels.